ANALISIS KESESUAIAN MATERI PADA LAMAN SLOEFUL.COM SEBAGAI MEDIA PEMBELAJARAN KETERAMPILAN MENYIMAK BAHASA JERMAN TINGKAT SMA KELAS XI SEMESTER 2 - Eni, Fitri Ning Suworo; Titaley, Audrey Gabriella (LATERNE, 2025)
Listening comprehension is a key aspect of learning the German language, as it supports both understanding and communication. Digital media such as sloeful.com, which features pronunciation audio, can effectively support the development of listening skills; however, the content provided must first be analyzed to ensure its alignment with the Merdeka Curriculum. This study aims to analyze the appropriateness of the Essen und Trinken materials on sloeful.com before their implementation as a learning medium. A descriptive qualitative method was employed, using content analysis techniques. The data sources included the Thematic Content Map and the materials available on the website. The results of the analysis indicate that the Essen und Trinken content on sloeful.com is generally appropriate and that its audio features can enhance students’ listening skills, although certain adjustments are still necessary to better contextualize the materials for use in senior high school instruction.